2019
DOI: 10.1128/mbio.02729-18
|View full text |Cite
|
Sign up to set email alerts
|

Peptidoglycan Remodeling Enables Escherichia coli To Survive Severe Outer Membrane Assembly Defect

Abstract: Gram-negative bacteria have a tripartite cell envelope with the cytoplasmic membrane (CM), a stress-bearing peptidoglycan (PG) layer, and the asymmetric outer membrane (OM) containing lipopolysaccharide (LPS) in the outer leaflet. Cells must tightly coordinate the growth of their complex envelope to maintain cellular integrity and OM permeability barrier function. The biogenesis of PG and LPS relies on specialized macromolecular complexes that span the entire envelope. In this work, we show that Escherichia co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
176
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 128 publications
(192 citation statements)
references
References 66 publications
(102 reference statements)
3
176
0
Order By: Relevance
“…The CPS export machinery must pass through the PG layer without compromising the essential integrity of the cell wall. The complexity of these systems and the importance of maintaining the PG barrier has recently been highlighted in the context of LPS translocation, where conditional depletion of the translocation machinery immediately activates a PG-editing enzyme complex (37). The nature of the interaction between OPX proteins and PG is unknown, but the noncovalent interaction of the ␤-barrel OM protein OmpA with PG has been studied in detail and residues have been identified that are important for PG association in OmpA and other PG-associated proteins (29,38).…”
Section: Discussionmentioning
confidence: 99%
“…The CPS export machinery must pass through the PG layer without compromising the essential integrity of the cell wall. The complexity of these systems and the importance of maintaining the PG barrier has recently been highlighted in the context of LPS translocation, where conditional depletion of the translocation machinery immediately activates a PG-editing enzyme complex (37). The nature of the interaction between OPX proteins and PG is unknown, but the noncovalent interaction of the ␤-barrel OM protein OmpA with PG has been studied in detail and residues have been identified that are important for PG association in OmpA and other PG-associated proteins (29,38).…”
Section: Discussionmentioning
confidence: 99%
“…FtsN mutants defective for either domain fail to localize to the cytokinetic ring or to reduce size when overexpressed (Figs 4 and 5). Apart from promoting cytokinesis, FtsN also activates PBP1b [64,74,75], a nonessential cell wall synthesis enzyme speculated to play a role in cell wall repair during normal growth of the E. coli peptidoglycan sacculus [46,[76][77][78]. Midcell enrichment of FtsN in acidic media may also augment PBP1b activity at the septum and thus direct it to the region with the highest rates of peptidoglycan synthesis.…”
Section: Ftsn As An Integration Point For Ph-dependent Changes In Celmentioning
confidence: 99%
“…It has been previously hypothesized that the formation of these complexes enables the cell to coordinate and regulate the activities of various synthetic and hydrolytic PG enzymes in a spatiotemporal manner (Höltje, 1993). Within these complexes, the key bifunctional penicillin-binding protein (PBP) PG synthases are activated by cognate outer membrane (OM)-anchored lipoproteins (Paradis-Bleau et al, 2010;Typas et al, 2010Typas et al, , 2012Dorr et al, 2014;Egan et al, 2014Egan et al, , 2018Greene et al, 2018;Moré et al, 2019) and coordinate their action with another, cell constriction-related protein complex (Gray et al, 2015). However, with the exception of the amidases (Uehara et al, 2010;Yang et al, 2012;Peters et al, 2013;Tsang et al, 2017), it is less clear how Gram-negative bacteria control the activities of their repertoire of hydrolases, i.e.…”
Section: Introductionmentioning
confidence: 99%